The effectiveness of a health promotion with group intervention by clinical trial. Study protocol - Campo Osaba Maria-Antonia; Del Val José-Luis; Lapena Carolina; Laguna Vicencia; García Araceli; Lozano Olga; Martín Ziortza; Rodriguez Rómulo; Borrás Enriqueta; Orfila Francesc; Tierno María Teresa (BMC, 2012)
Abstract Background The promotion of health and the interventions in community health continue to be one of the pending subjects of our health system. The most prevalent health problems (cardiovascular diseases, cancer, diabetes...) are for the most part related to life habits. We propose a holistic and integral approach as the best option for tackling behavior and its determinants. The research team has elaborated the necessary educational material to realize group teaching, which we call "Health Workshops". The goal of the present study is to evaluate the effectiveness of these Health Workshops in the following terms: Health Related Quality of Life (HRQOL), incorporate and maintain a balanced diet, do physical activity regularly, maintain risk factors such as tension, weight, cholesterol within normal limits and diminish cardiovascular risk. Methods/Design Controlled and random clinical testing, comparing a group of persons who have participated in the Health Workshops with a control group of similar characteristics who have not participated in the Health Workshops. Field of study: the research is being done in Health Centers of the city of Barcelona, Spain. Population studied: The group is composed of 108 persons that are actually doing the Health Workshops, and 108 that are not and form the control group. They are assigned at random to one group or the other. Data Analysis: With Student's t-distribution test to compare the differences between numerical variables or their non parametric equivalent if the variable does not comply with the criteria of normality. (Kolmogorov-Smirnof test). Chi-square test to compare the differences between categorical variables and the Logistic Regression Model to analyze different meaningful variables by dichotomous analysis related to the intervention. Discussion The Health Workshop proposed in the present study constitutes an innovative approach in health promotion, placing the emphasis on the person's self responsibility for his/her own health. The rhythm of a weekly session during 8 weeks with recommended activities to put into practice, as well as the support of the group is an opportunity to incorporate healthy habits and make a commitment to self-care. The sheets handed out are a Health Manual that can always be consulted after the workshop ends. Trial registration Clinical Trials.gov Identifier: NCT01440738